The Effectiveness of Differentiated Instruction in Economics Education Learning among Students of the Economics Education Study Program at Institut Pendidikan Tapanuli Selatan - Dinda Vebrina; Laila Surayya (Edupedia Publisher, 2026)
Purpose – This study examined the effectiveness of differentiated instruction in economics education among students of the Economics Education Study Program at Institut Pendidikan Tapanuli Selatan. The study addressed the need for adaptive and student-centered instruction that accommodates differences in students’ readiness, interests, and learning preferences. Methodology – A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. Participants were undergraduate students divided into an experimental group receiving differentiated instruction and a control group receiving conventional instruction. Data were collected through learning achievement tests, student engagement questionnaires, and classroom observations, then analyzed using descriptive statistics, paired-sample t-tests, and independent-sample t-tests with SPSS. Findings – Differentiated instruction significantly improved students’ learning outcomes and classroom engagement. The experimental group achieved higher posttest scores and demonstrated greater participation than the control group. The findings indicate that flexible learning pathways tailored to students’ diverse learning profiles enhance conceptual understanding and improve the quality of learning in economics education. Novelty – This study provides empirical evidence of the effectiveness of differentiated instruction in higher education economics by demonstrating how adaptive learning strategies accommodate student diversity and improve both academic achievement and engagement. Significance – The findings benefit university lecturers, curriculum developers, and higher education institutions by providing evidence to support the adoption of differentiated instructional strategies for creating more inclusive, meaningful, and student-centered learning environments.